(untitled) (Communications in Mathematical Research, 2021)
In this paper, we give an estimate result of Gol'dberg's theorem concerning the growth of meromorphic solutions of algebraic differential equations by using Zalcman Lemma. It is an extending result of the corresponding theorem by Yuan et al. (Yuan W J, Xiao B, Zhang J J. The general theorem of Gol'dberg concerning the growth of meromorphic solutions of algebraic differential equations. Comput. Math. Appl., 2009, 58: 1788–1791). Meanwhile, we also take some examples to show that our estimate is sharp.